24-Hour Urine Calcium Oxalate Supersaturation Risk Correlates with Computerized Tomography Volumetric Calcium Oxalate Stone Growth. Issue 6 (21st December 2021) - Yuzhakov, Stanislav; Steadman, Shavano D.; Otto, Brandon J.; Bird, Vincent G.; Canales, Benjamin K.
Abstract : Purpose: In vitro experiments demonstrate calcium oxalate (CaOx) supersaturation (SS) drives CaOx nucleation and growth. We investigated the link between 24-hour urine SS CaOx and in vivo stone growth through a natural history, imaging study. Materials and Methods: Using an institutional review board-approved database, we sought >80% CaOx stone formers who prior to stone intervention obtained 2 separate computerized tomography (CT) scans with at least one 24-hour urine collection between scans. Two blinded reviewers calculated bilateral 3-dimensional stone volume using the Visage 7® region of interest pen tool. CT volume difference was divided by time between scans, and SS CaOx was grouped into low (<5), medium (5–10) and high risk (>10). Statistical significance between groups was assessed by Kruskal-Wallis test. Results: We identified 80 individuals with stone growth measured by 3-dimensional CT (mean ∼7 months between studies). Inter-reviewer reliability of CT volume measurement was well correlated (0.98, Gwet's AC2), and an arbitrator was only needed in 13/160 (8%) cases. Median stone volume growth/year was 15%, 71% and 177% for low, medium and high risk groups, respectively (p <0.001). Despite inter-individual variation, best fit of mean SS CaOx vs stone volume growth was moderately correlated (Spearman's rho=0.53, p <0.001). Conclusions: In a population of pure CaOx stone formers, increased 24-hour SS CaOx risk was associated with increased in vivo stone growth. Further investigations using CT volumetric stone growth may allow for the noninvasive study of stone growth modulators, improved stone risk prediction and development of a kidney stone simulator.